Modelling User Behavior Towards Smartphones and Wearable Technologies: A Bibliometric Study and Brief Literature Review - Jamalova, Maral (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The study employs bibliometric and content analysis to assess the current status of applying technology adoption models (such as the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Innovation Diffusion Theory (IDT)) to the smartphone market, which also encompasses smart wearables. Hereby, the author aims to explore the relationship between smartphone usage and adoption models and contribute to the literature through current trends and methodologies. To achieve the goal, the author applied a two-stage approach. In the first stage, 213 articles were analyzed using citation and bibliographic coupling tools in VOS viewer (version 1.6.20). The papers were selected from the Scopus database, and the search was conducted in the fields of economics, business, and computer technologies. In the second stage, the author conducted a brief literature review of the most influential papers. The results illustrate the situation regarding the implementation of various models in the case of smartphone adoption. Content analyses of the most influential papers were conducted to elucidate and enhance the findings of bibliometric analyses, identify research gaps, and guide future research development.